Genetic Association of Finger Photoplethysmography-Derived Arterial Stiffness Index With Blood Pressure and Coronary Artery Disease. Issue 6 (June 2019) - Zekavat, Seyedeh M.; Aragam, Krishna; Emdin, Connor; Khera, Amit V.; Klarin, Derek; Zhao, Hongyu; Natarajan, Pradeep
Abstract : Objective—: Arterial stiffness index (ASI) is independently associated with blood pressure (BP) and coronary artery disease (CAD) epidemiologically. However, it is unknown whether these associations represent causal relationships. Here, we assess whether genetic predisposition to increased ASI is associated with elevated BP and CAD risk. Approach and Results—: We first performed a large-scale epidemiological association of finger photoplethysmography-derived ASI in the UK Biobank, finding significant associations with systolic BP (β=0.55 mm Hg; [95% CI, 0.45–0.65]; P =5.77×10 −24 ; N=137 858), diastolic BP (β=1.05 mm Hg; [95% CI, 0.99–1.11]; P =7.27×10 −272 ; N=137 862), and incident CAD (hazard ratio, 1.08; [95% CI, 1.04–1.11]; P =1.5×10 −6 ; N=3692 cases, 126 615 controls) in multivariable models. We then performed an ASI genome-wide association study analysis in 131 686 participants from the UK Biobank. Across participants not in the ASI genome-wide association study, a 6-variant ASI polygenic risk score was calculated. Each SD increase in genetic ASI was associated with systolic BP (β=4.63 mm Hg; [95% CI, 2.1–7.2]; P =3.37×10 −4 ; N=208 897), and diastolic BP (β=2.61 mm Hg; [95% CI, 1.2–4.0]; P =2.85×10 −4 ; N=208 897); however, no association was observed with incident CAD (hazard ratio, 1.12; [95% CI, 0.55–2.3]; P =0.75; N=223 061; 7534 cases). The lack of CAD association observed was replicated among 184 305 participants (60 810 cases) from the CARDIOGRAMplusC4D (Coronary Artery Disease Genetics Consortium; odds ratio, 0.56; [95% CI, 0.26–1.24]; P =0.15). Conclusions—: Our data support the conclusion that finger photoplethysmography-derived ASI is an independent, genetically causal risk factor for BP, but do not support the notion that ASI is a suitable surrogate for CAD risk. Abstract : Supplemental Digital Content is available in the text.